Hyperosmotic stress induces cell cycle arrest in retinal pigmented epithelial cells - Arsenijevic, T (Nature Publishing Group, 2013)
Osmotic changes occur in many tissues and profoundly influence cell function. Herein, we investigated the effect of hyperosmotic stress on retinal pigmented epithelial (RPE) cells using a microarray approach. Upon 4-h exposure to 100 mM NaCl or 200 mM sucrose, 79 genes were downregulated and 72 upregulated. Three gene ontology categories were significantly modulated: cell proliferation, transcription from RNA polymerase II promoter and response to abiotic stimulus. Fluorescent-activated cell sorting analysis further demonstrated that owing to hyperosmotic stimulation for 24 h, cell count and cell proliferation, as well as the percentage of cells in G0/G1 and S phases were significantly decreased, whereas the percentage of cells in G(2)/M phases increased, and apoptosis and necrosis remained unaffected. Accordingly, hyperosmotic conditions induced a decrease of cyclin B1 and D1 expression, and an activation of the p38 mitogen-activated protein kinase. In conclusion, our results demonstrate that hypertonic conditions profoundly affect RPE cell gene transcription regulating cell proliferation by downregulation cyclin D1 and cyclin B1 protein expression.